Effects of Maternal Caffeine Consumption on Ovarian Follicle Development in Wistar Rats Offspring - M Dorostghoal; M Khaksari Mahabadi; S Adham (JRI, 2011)
Background: In recent years concerns have been raised about human reproductive disorders, specially the effects of environmental factors on human fertility and pregnancy outcome. Therefore, the present study was designed to assess the effects of maternal caffeine consumption on ovarian follicles development in rat offspring. Methods: 60 pregnant female rats were randomly divided into a control and two experimental groups. The rats in the two experimental groups received caffeine via drinking water during gestation (26 and 45 mg/kg) and lactation (25 and 35 mg/kg). The ovaries of the offspring were removed at 7, 14, 28, 60, 90 and 120 days after birth, and fixed in Bouin’s solution. By preparing serial tissue sections, structural changes in ovarian follicles and corpora lutea were studied during postnatal development. Results: The weight of ovaries decreased significantly (p<0.05) in the high dose caffeine-treated group at all stages of postnatal development. Significant (p<0.05) decreases were seen in the number of primordial follicles from day 7 to 120 after birth in the high dose caffeine-treated group. Moreover, the number of primary and secondary follicles decreased significantly on days 7, 14 and 28 as did the number of antral follicles on days 14 and 28 after birth (p<0.05) in the high dose caffeine-treated group. The diameter of secondary and antral follicles decreased significantly (p<0.05) in high dose caffeine-treated group on the early days of postnatal development. No statistically significant differences were seen in the number of corpora lutea between the groups. Conclusion: The present study shows that caffeine consumption during gestation and lactation affects the early stages of ovarian follicle development and reduces reproductive efficiency in the offspring of Wistar rats.
Keywords: Caffeine, Fertility, Ovarian follicles, Postnatal development